2005
DOI: 10.2176/nmc.45.423
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Brain Metastasis From Renal Cell Carcinoma 15 Years After Nephrectomy-Case Report-

Abstract: A 77-year-old man presented with a metastatic brain tumor 15 years after nephrectomy for a renal cell carcinoma. Neurological examination showed recent memory disturbance and slight right hemiparesis. Magnetic resonance imaging revealed a round well-demarcated mass extending from the left thalamus to the left trigone of the lateral ventricle. Preoperative angiography showed tumor staining. Surgery was performed by opening the inferior temporal sulcus. Only biopsy could be performed because of extensive bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…Another hypothesis is that adjuvant therapy for renal cell carcinoma decreases host immunopotency and thus leads to faster development of brain lesions. 16 In the present report, the patient evaluated initially did not present central nervous system impairment: it was only after some years that it was found that he had brain metastasis.…”
Section: 3mentioning
confidence: 47%
See 2 more Smart Citations
“…Another hypothesis is that adjuvant therapy for renal cell carcinoma decreases host immunopotency and thus leads to faster development of brain lesions. 16 In the present report, the patient evaluated initially did not present central nervous system impairment: it was only after some years that it was found that he had brain metastasis.…”
Section: 3mentioning
confidence: 47%
“…1 The treatment may be difficult because central nervous system lesions are usually resistant to chemotherapy and radiotherapy. 15 Nonetheless, these lesions may respond to immunotherapy using alpha-interferon 16 or interleukin (IL)-2. After treatment of brain metastases, the median survival is about 4-5 months, 3 but aggressive surgical resection significantly increases this period.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter one is less frequently seen and most of them are benign lesions such as colloid cysts and choroid plexus papillomas. Although the choroid plexus is highly vascularized and theoretically is vulnerable to metastasis, a few cases have been reported (2,4,6,7,9). In those cases it is very rare for metastases to mimic a colloid cyst as in our case and to our knowledge only three cases have been previously reported.…”
Section: Karatay M Et Al: Renal Cell Carcinoma Metastasis To the Thimentioning
confidence: 53%
“…Involvement of the ventricular system is not common and it is almost always associated with multiple brain metastases when it occurs (1,3,4). Solitary metastasis to the ventricular system and especially to the third ventricle is very rare (6,7,9). The most common solitary lesions of the third ventricle are colloid cyst and choroid plexus papilloma (5).…”
Section: Introductionmentioning
confidence: 99%